Pirates, Merchants, Settlers, and Slaves : Colonial America and the Indo-Atlantic World. - McDonald, Kevin P., 1972- (University of California Press, 2015)
"In the late seventeenth and early eighteenth centuries, more than a thousand pirates poured from the Atlantic into the Indian Ocean. There they helped launch an informal trade network that spanned the Atlantic and Indian Ocean worlds, connecting the North American colonies with the rich markets of the East Indies. Rather than conducting their commerce through chartered companies based in London or Lisbon, colonial merchants in New York entered into an alliance with Euro-American pirates based in Madagascar. Pirates, merchants, settlers, and slaves explores the resulting global trade network located on the bperipheries of world empires and shows the illicit ways American colonists met the consumer demand for slaves and East India goods. The book reveals that pirates played a significant yet misunderstood role in this period and that seafaring slaves were both commodities and essential components in the Indo-Atlantic maritime networks."--Provided by publisher.
"The Fletcher Jones Foundation Humanities Imprint"--Page [v].
Keywords: Slave trade -- United States -- History -- 17th century.; Slave trade -- United States -- History -- 18th century.; Pirates -- United States -- History -- 17th century.; Pirates -- United States -- History -- 18th century.; Esclaves -- Commerce -- États-Unis -- Histoire -- 17e siècle.; Esclaves -- Commerce -- États-Unis -- Histoire -- 18e siècle.; Pirates -- États-Unis -- Histoire -- 17e siècle.; Pirates -- États-Unis -- Histoire -- 18e siècle.; HISTORY -- United States -- State & Local -- General.; HISTORY -- World.; Pirates; Slave trade; United States; 1600-1799; 17th century world history.; 18th century world history.; american history.; atlantic ocean.; california world history series.; colonial america.; colonial merchants.; colonialism.; consumer demands.; early american commerce.; east indies.; euro american pirates.; global trade.; history.; indian ocean.; informal trade network.; merchant ships.; north american colonies.; north atlantic slave trade.; piracy.; pirates.; retrospective.; sailors.; seafarers.; seafaring.; slave trade.; slavery.; transoceanic network.; world empires.; world history.; History